Provision of arak bali reduces spermatozoa quality of white rats (rattus norvegicus) - Antari, Ni Wayan Sukma; Hayati, Alfiah; Winarni, Dwi (Folia Medica Indonesiana, 2017)
This study aimed to determine the effect of arak bali on the quality of spermatozoa include morphology, motility, viability, membrane integrity of spermatozoa rat (Rattus norvegicus). The study was conducted in two phases: the first phase of the deployment of questionnaires conducted in five districts in Bali to determine the type and frequency of arak bali consumption and phase II made arak bali giving treatment in experimental animals. This study used 24 male rats (170-200 grams), divided into four groups: one control and three treatments (by arak bali containing 40% alcohol as much as 0.1 and 0.5 mL and 0.1 mL much alcohol synthesis, for 45 days. the results showed that of the five districts in Bali, most people consume arak bali commercial and most of the frequency of consumption of the week more than one bottle (350 mL). the provision of arak bali in experimental animals, degrade the quality (morphology, motility, viability, membrane integrity), the greater the volume given declining spermatozoa quality.